Real materialism and other essays - Strawson, Galen (Oxford : Clarendon, 2008)
This is a collection of essays on a set of related topics in philosophy of mind and metaphysics - consciousness and the mind-body problem, our knowledge of the world, the nature of the self or subject, free will and moral responsibility, the nature of thought and intentionality, and causation and David Hume.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy, Modern -- 21st century